Integrating the 6Cs of the 21st Century Education into the English Lesson and the School Literacy Movement in Secondary Schools - Anugerahwati, M (KnE Social Sciences, 2019)
In the face of the 21st Century education, the concept of the 6 Cs is becoming more and more popular among educators. Schools now are striving to educate their students to achieve the competences of thinking critically and solving real-world problems, conducting clear communication, having collaborative practices, respecting culture, developing creativity, and making good use of connectivity. But what do they mean? This paper proposes some ways the 6Cs can, and should, be integrated in the English lessons, particularly in secondary schools. The suggestions refer to ways of integrating the 6Cs in relation with the Strengthening of Character Education currently being implemented in secondary schools, in line with the nine priorities of the President. Keywords: 21st century education, the 6 Cs, English lesson